2023
DOI: 10.1002/jmv.28660
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hospitalization and sequelae in patients with COVID‐19 treated with 3‐day early remdesivir vs. controls in the vaccine and Omicron era: A real‐life cohort study

Abstract: Recently, a benefit from administration of a 3-day course of early remdesivir (ER) in the outpatients' setting was reported. However, real-life data on its use is scarce.Therefore, we explored the ER clinical outcome in our outpatients' s cohort, compared to untreated controls. We included all patients who were prescribed ER from February to May 2022 and followed them up for 3 months and compared patients who received treatment with untreated controls. In the two groups the following outcomes were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
(116 reference statements)
0
3
1
Order By: Relevance
“…These findings suggest that both azvudine and nirmatrelvir/ritonavir have an overall favorable safety profile for the treatment of COVID-19 patients, which aligns with the results of a recent meta-analysis involving 2,143 patients (Amani and Amani, 2023). From the incidence of adverse events perspective, our data, albeit limited, suggested an overall lower frequency of adverse events compared to clinical trials or other cohort studies (Gentile et al, 2022;Amani and Amani, 2023;Mazzitelli et al, 2023a;Cheema et al, 2023;Gao et al, 2023). For example, in a phase 2-3 doubleblind, randomized, controlled trial, the incidence of any adverse events during the treatment period was higher with nirmatrelvir/ Frontiers in Pharmacology frontiersin.org ritonavir compared to placebo (22.6% vs. 23.9%), while serious adverse events were 1.6% vs. 6.6% (Amani and Amani, 2023).…”
Section: Discussioncontrasting
confidence: 46%
“…These findings suggest that both azvudine and nirmatrelvir/ritonavir have an overall favorable safety profile for the treatment of COVID-19 patients, which aligns with the results of a recent meta-analysis involving 2,143 patients (Amani and Amani, 2023). From the incidence of adverse events perspective, our data, albeit limited, suggested an overall lower frequency of adverse events compared to clinical trials or other cohort studies (Gentile et al, 2022;Amani and Amani, 2023;Mazzitelli et al, 2023a;Cheema et al, 2023;Gao et al, 2023). For example, in a phase 2-3 doubleblind, randomized, controlled trial, the incidence of any adverse events during the treatment period was higher with nirmatrelvir/ Frontiers in Pharmacology frontiersin.org ritonavir compared to placebo (22.6% vs. 23.9%), while serious adverse events were 1.6% vs. 6.6% (Amani and Amani, 2023).…”
Section: Discussioncontrasting
confidence: 46%
“…A comparison with an untreated control group would offer significant information. Mazzitelli et al, in Italy, compared 3RDV to no treatment in a large real-world cohort and found that the use of 3RDV would reduce the risk of hospitalization by 95% and the duration of positivity and symptoms by eight and five days, respectively [ 39 ]. Similarly, a recent observational study from Greece compared NMV/r to no treatment and showed that in the first group, only 1.5% required eventual hospitalization, compared to a staggering 55.5% in the control group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some antiviral treatment medications, such as ivermectin, which has recently received FDA approval, chloroquine, remdesivir, ribavirin, and lopinavir/ritonavir, among others, have been used to treat individuals who have SARS-CoV-2 infections. However, an effective and specific anti-SARS-CoV-2 drug is still to be identified [48] On the other hand, retrospective data from studies conducted in Italy show that early hospitalization and early use of remdesivir may reduce COVID-19 progression to more severe respiratory disease and provide clinical benefit in patients with COVID-19 [48][49][50].…”
Section: Introductionmentioning
confidence: 99%